Loss of Lamin A leads to the nuclear translocation of AGO2 and compromised RNA interference - Lobo, Vivian; Nowak, Iwona; Fernandez, Carola; Correa Muler, Ana Iris; Westholm, Jakub O; Huang, Hsiang-Chi; Fabrik, Ivo; Huynh, Hang T; Shcherbinina, Evgeniia; Poyraz, Melis; Härtlova, Anetta; Benhalevy, Daniel; et al. (Nucleic acids research, 2024)
In mammals, RNA interference (RNAi) was historically studied as a cytoplasmic event; however, in the last decade, a growing number of reports convincingly show the nuclear localization of the Argonaute (AGO) proteins. Nevertheless, the extent of nuclear RNAi and its implication in biological mechanisms remain to be elucidated. We found that reduced Lamin A levels significantly induce nuclear influx of AGO2 in SHSY5Y neuroblastoma and A375 melanoma cancer cell lines, which normally have no nuclear AGO2. Lamin A KO manifested a more pronounced effect in SHSY5Y cells compared to A375 cells, evident by changes in cell morphology, increased cell proliferation, and oncogenic miRNA expression. Moreover, AGO fPAR-CLIP in Lamin A KO SHSY5Y cells revealed significantly reduced RNAi activity. Further exploration of the nuclear AGO interactome by mass spectrometry identified FAM120A, an RNA-binding protein and known interactor of AGO2. Subsequent FAM120A fPAR-CLIP, revealed that FAM120A co-binds AGO targets and that this competition reduces the RNAi activity. Therefore, loss of Lamin A triggers nuclear AGO2 translocation, FAM120A mediated RNAi impairment, and upregulation of oncogenic miRNAs, facilitating cancer cell proliferation.
Keywords: RNA Interference; Lamin Type A; RNA-Binding Proteins; Argonaute Proteins; aktivní transport - buněčné jádro; Humans; Cell Nucleus; buněčné jádro; Melanoma; proteiny vázající RNA; RNA interference; MicroRNAs; proliferace buněk; lidé; Cell Line, Tumor; mikro RNA; melanom; lamin typ A; Cell Proliferation; Argonaut proteiny; Active Transport, Cell Nucleus; nádorové buněčné linie